Chemical mechanism of formation of two-dimensional electron gas at the Al2O3/TiO2 interface by atomic layer deposition - Park, Jeongwoo; Eom, Hyobin; Kim, Seong Hwan; Seok, Tae Jun; Park, Tae Joo; Lee, Sang Woon; Shong, Bonggeun (Materials Today Advances, 2021)
Two-dimensional electron gases (2DEGs) localized at oxide heterointerfaces can potentially be used in applications associated with the design of novel electronic device architectures. Recent studies have reported that atomic layer deposition (ALD) of Al2O3 on TiO2 substrates can generate 2DEG states, owing to in situ formation of interfacial oxygen vacancies (VO). However, the chemical mechanism governing the adsorption of the trimethylaluminum (TMA) precursor on the TiO2 surface remains unclear. In this work, an investigation aimed at elucidating the formation of the 2DEG state through the reaction of TMA on TiO2 was performed using periodic dispersion-corrected DFT + U calculations. Dimethylether, whose desorption leaves VO surrounded by Ti3+, can be formed via direct methylation of the lattice oxygen on the TiO2 surface. The experimentally observed dependence of the carrier density on the process temperature of Al2O3 ALD confirmed the endothermic nature of VO formation. Furthermore, the emergence of geometrically confined n-type electronic states corresponding to interfacial VO confirmed the formation of 2DEGs at the heterointerface. Our study provides a fundamental understanding of 2DEG formation in the Al2O3/TiO2 heterojunction interface.
Keywords: 2021 the author two-dimensional electron gas; Atomic-layer deposition; Chemical mechanism; Electronics devices; Gas state; Hetero-interfaces; Localised; Mechanism of formation; Trimethylaluminum; Two-dimensional electron gas; 2DEG; Adsorption; ALD; Alumina; Anatase; Surface chemistry